A simple Christmas on the farm - Alsdurf, Phyllis, 1950- (Beaming Books, 2021)
A young girl is skeptical when her parents declare they will have a simple Christmas focused on giving rather than getting, but soon their old barn is filled with food, fun, friends, and homemade gifts. Includes directions for making star ornaments, Christmas card coasters, and melted crayon rocks.